Studi In Vitro dan In Silico pada Ekstrak Bonggol Pisang Kepok sebagai Anti-tirosinase - Andini, Andini; Raharjo, Sentot Joko; Misgiati, Misgiati; Izza, Aqidatul; Istiana, Meiria (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2024)
Tyrosinase is a critical enzyme in melanin synthesis, where its overactivity can result in hyperpigmentation disorders. Despite the availability of synthetic tyrosinase inhibitors, concerns about safety have prompted the search for natural alternatives. The objective of this study is to evaluate the potential of Kepok banana (Musa acuminata x balbisiana) corm extract as a natural tyrosinase inhibitor, using in vitro and in silico approaches. The extract was prepared by maceration with etanol 96%, followed by sonication and lyophilization. LC-MS analysis was performed on a Shimadzu LCMS 8040 using a Shim Pack FC ODS column with 90% methanol as the mobile phase under isocratic conditions. Samples were ionized via ESI in positive mode and scanned over m/z 10–1000. Peaks were identified based on their m/z values and MS/MS fragmentation patterns. In vitro and in silico analyses were applied, respectively, to study the biological process of kepok banana corm extract as a natural tyrosinase inhibitor. The result of the kepok banana corm extraction process was 12.5% dry powder with bioactive components identified via LC-MS, including flavonoids, phenolics, and terpenoids. The kepok banana corm ethanol extract exhibited strong tyrosinase inhibition with an IC₅₀ of 91.074 µg/mL, falling below the 100 µg/mL threshold for strong inhibitors and showing a similar inhibition pattern to the standard kojic acid (IC₅₀ = 10.87 µg/mL). Molecular docking revealed that major compounds, particularly flavonoids, exhibited high binding affinity with the tyrosinase enzyme through hydrogen bonding and hydrophobic interactions, similar to kojic acid, a known inhibitor. These findings suggest that kepok banana corm extract may serve as a promising natural tyrosinase inhibitor, with potential applications in hyperpigmentation treatment and cosmetic formulations.